Palynology and palynofacies studies in the lowermost Jurassic of the Lusitanian Basin (Pereiros Formation of the Silves Group), Portugal: evidence of the first transgressive episode - Margarida Vilas-Boas; Zélia Pereira; Simonetta Cirilli; Luís Vítor Duarte; Sérgio Luis Rodrigues Sêco; Paulo Fernandes (Acta Palaeobotanica, 2023)
The Silves Group of the Lusitanian Basin in Portugal represents the initial infill of the continental rifting basins that formed during the breakup of northern Pangaea regions. Evaporites, especially halite, mark the transition from continental to marine settings and the beginning of the deposition in passive margin basins. This work presents the results of the palynostratigraphic and palynofacies analysis of two partial sections from the Pereiros Formation at the top of the Silves Group. The two sections are composed of sandstones, mudstones and dolostones interpreted as deposited in fluvial and lacustrine settings without apparent marine influence. The palynological content is diverse and wellpreserved, dating both sections to the early Hettangian (Lower Jurassic), indicated by the presence of spores Ischyosporites variegatus, Kraeuselisporites reissingeri, Porcellispora longdonensis and the pollen grains Perinopollenites elatoides and Pinuspollenites minimus. The palynological content of one of the sections (Lamas I) is noticeable by microforaminifera linings, suggesting evidence for a hitherto marine incursion at this age in the Silves Group stratigraphy. The beds that yielded the microforaminifera linings are interpreted as having been deposited in an estuarine-type setting, created by the first and short-lived marine transgressive event in the Lusitanian Basin during the early Hettangian.